LEARNING ANALYSIS INDICATING SOCIAL AND RELIGIOUS VALUES FOR STUDENTS IN ISLAMIC BOARDING SCHOOLS - Suwandi; Muhammad Yusuf Siregar (Journal of Educational Science Learning and Research, 2024)
The aim of this research is to identify learning to instill social and religious values ​​for students in Islamic boarding schools. The approach used in this research is a descriptive qualitative approach, observation, interview and documentation methods. The results of this research can be explained that the use of various methods in developing the cultivation of social and religious values, namely by telling stories about the virtues of prayer, prayers after prayer, prayers for both parents, children are able to know the creation of Allah SWT, know the names of prophets and duties, daily prayers and the practice of morning prayers to carry out religious activities, practicing alms and saving to carry out good deeds, politeness in behaving towards older people, saying hello and shaking hands. Judging from several of these activities, the instillation of social and religious values ​​for students in Islamic boarding schools is well planned and implemented. There are several methods that can develop the cultivation of social and religious values, namely the storytelling method, field trip method, demonstration method, assignment method, habituation method, and conversation method.